2014
DOI: 10.1007/s12031-014-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Fragmentation Has Differential Effects on Obese and Lean Mice

Abstract: Summary Chronic sleep fragmentation (SF), common in patients with sleep apnea, correlates with the development of obesity. We hypothesized that SF differentially affects neurobehavior in lean wildtype (WT) and obese pan-leptin receptor knockout (POKO) mice fed the same normal diet. First we established an SF paradigm by interrupting sleep every 2 min during the inactive light span. The maneuver was effective in decreasing sleep duration and bout length, and in increasing sleep state transition and waking, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…This could be due to circadian activity abnormality or behavioral changes, including anxiety or depression, which has been reported before [39, 40]. Therefore, we explored circadian activity including gene expression of circadian genes, as well as neurobehavior in the MLP-exposed offspring.…”
Section: Resultsmentioning
confidence: 79%
“…This could be due to circadian activity abnormality or behavioral changes, including anxiety or depression, which has been reported before [39, 40]. Therefore, we explored circadian activity including gene expression of circadian genes, as well as neurobehavior in the MLP-exposed offspring.…”
Section: Resultsmentioning
confidence: 79%
“…Studies in CB1 KO mice have found significantly reduced NREM bout duration with an increased number of NREM bouts [ 24 , 25 ]. REM sleep is consistently reduced following administration of CB1 antagonists [ 28 , 29 , 32 , 79 , 80 ], and reduced REM sleep is frequently associated with NREM fragmentation [ 67 , 68 ]. In the present study, reductions in REM sleep time were associated with time points where there was noticeable fragmentation of NREM.…”
Section: Discussionmentioning
confidence: 99%
“…A recent animal study suggests that sleep deprivation differentially impacts obese vs lean animals on pain sensitivity; when sleep was fragmented, pain threshold was increased in the lean but not in obese mice at one of the testing times during a day. 102 Interestingly, successful treatment of OSA may have a positive impact on pain. A small study testing elderly OSA patients with high-vs low-capacity continuous positive airway pressure (CPAP) therapy 103 found that those who received high-capacity CPAP had significantly increased pain tolerance to electrical stimulation, whereas there was no change in those receiving low-capacity CPAP.…”
Section: Potential Mechanisms Underlying the Obesity–pain Linkmentioning
confidence: 99%